ACTIVE LABOUR MARKET POLICIES IN SLOVAKIA IN 2007-2017 - Karasova, Katarina; Balaz, Vladimir; Chrancokova, Martina (Economic and Social Development: Book of Proceedings, 2018)
The research analyses the performance of active labour market policies (ALMP) in Slovakia in 2007-2017. We found limited evidence of the economic efficiency of the ALMP in Slovakia. We quantify the relative importance of the ALMP compared to other factors for the employability of job seekers. ALMP performance relates to a host of external factors, such as business cycles, the number of local job vacancies, discrimination towards some ethnic minorities, and levels of regional development. We examined the success of the ALMP via logistic regression. The regression analysis concentrated on job seekers' rate of repeated registration with the Central Office for Labour, Social Affairs and Family (COLSAF). Males were less likely to re-register with the COLSAF. Older job seekers were more likely to re-register. Education was an extremely important factor of employability. The negative coefficient for the educational level indicates that job seekers with the lowest level of education had the highest chance of re-registering. The positive coefficient for the length of instruments implies that job seekers with long stays in the ALMP instrument(s) were more likely to re-register. As for the specific ALMP, education, age, regional development levels and the situation in regional labour markets were important predictors of repeated registration with the COLSAF. The highest beta values for the GDP growth rates were associated with instruments aimed and retraining. These instruments operated in a period of an economic boom (2014-2016). The business cycle was important for ALMP performance. Future ALMP will have to address challenges different from those in the 1990s and 2000s. The policies oriented towards labour supply would rise in importance. The future application of ALMP will be subject to (1) their economic and social efficiency, (2) demographic developments in the labour market, and (3) structural changes in the Slovak economy.